Missense mutation of a class B heat shock factor is responsible for the tomato bushy root-2 phenotype - Kevei, Zoltan; Silva Ferreira, Demetryus; Perez Casenave, Cristina Maria; Kurowski, Tomasz J.; Mohareb, Fady R.; Rickett, Daniel; Stain, Chris; Thompson, Andrew J. (BioMed Central, 2022)
The bushy root-2 (brt-2) tomato mutant has twisting roots, and slower plant development. Here we used whole genome resequencing and genetic mapping to show that brt-2 is caused by a serine to cysteine (S75C) substitution in the DNA binding domain (DBD) of a heat shock factor class B (HsfB) encoded by SolycHsfB4a. This gene is orthologous to the Arabidopsis SCHIZORIZA gene, also known as AtHsfB4. The brt-2 phenotype is very similar to Arabidopsis lines in which the function of AtHsfB4 is altered: a proliferation of lateral root cap and root meristematic tissues, and a tendency for lateral root cap cells to easily separate. The brt-2 S75C mutation is unusual because all other reported amino acid substitutions in the highly conserved DBD of eukaryotic heat shock factors are dominant negative mutations, but brt-2 is recessive. We further show through reciprocal grafting that brt-2 exerts its effects predominantly through the root genotype even through BRT-2 is expressed at similar levels in both root and shoot meristems. Since AtHsfB4 is induced by root knot nematodes (RKN), and loss-of-function mutants of this gene are resistant to RKNs, BRT-2 could be a target gene for RKN resistance, an important trait in tomato rootstock breeding.
Keywords: Bushy root-2; Genetic mapping; HsfB4; Root knot nematode resistance; SCHIZORIZA; Tomato